Mobilisations et conflits liés à la maitrise de l'urbanisation autour des industries à risque - Clara Osadtchy (Territoire en Mouvement)
This paper analyzes the processes that lead residents of an industry at risk to mobilize against a new planning tool that aims to secure the riparian areas and to limit and contain the danger at the root. To analyze the conflict as stories with their effects and meanings is necessary to understand relationship between population, territory and local policies. What are the spatial and territorial characteristics of this mobilization? Why is there an opposition to the Plan of Prevention of technological risks (PPRT), whose goal is supposedly environmental, and aims at the reduction of risks and the protection of the population? Who are the people involved in this process of information and how do they participate in this process? Does this mobilization participate in a renewal of the relationship between territory and industry?The survey is based on the case of the PPRT of an oil refinery located in the Bouches-du-Rhône, highly contested locally. Starting with a description of the mobilization of the inhabitants, this article studies the mechanisms of emergence, protesters claims, territorial effects and the consequences on institutions.